2020
DOI: 10.9734/ajmah/2020/v18i730224
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin and Hydroxychloroquine Accelerate Recovery of Outpatients with Mild/Moderate COVID-19

Abstract: Aims: The challenge regarding COVID-19 is to prevent complications and fatal evolution. Azithromycin (AZM) and hydroxychloroquine (HCQ) have proven their antiviral effect in vitro. We aimed to assess the efficacy and safety of AZM alone or combined to HCQ, prescribed, at an early stage, in patients with Covid-19, in a primary care setting. Study Design: Retrospective observational study. Place and Duration of Study: Patients have been followed by private practitioners in France, between March and A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…31 As noted above, several recent studies have attempted to explore the role of hydroxychloroquine earlier in the clinical course of COVID-19. [10][11][12][13][14] However, given enrollment of generally younger patients with low baseline rates of hospitalization, these studies appear under-powered to demonstrate meaningful effects. For example, the recent Spanish randomized trial explored early hydroxychloroquine use, at a median time from symptom onset of 3 days, in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 As noted above, several recent studies have attempted to explore the role of hydroxychloroquine earlier in the clinical course of COVID-19. [10][11][12][13][14] However, given enrollment of generally younger patients with low baseline rates of hospitalization, these studies appear under-powered to demonstrate meaningful effects. For example, the recent Spanish randomized trial explored early hydroxychloroquine use, at a median time from symptom onset of 3 days, in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…12 A small French report noted a reduction in symptoms with early therapy compared to observation. 13 Finally, a German report of 141 outpatients, when compared to cases in the community, noted a decrease in hospitalization rate (2.8% vs 15.4%) with a combination of hydroxychloroquine, azithromycin and zinc. 14 In summary, the majority of studies, although underpowered to show differences, are all directionally in favor of a reduced hospitalization rate with early outpatient treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Studies that assess azithromycin monotherapy versus standard of care in hospitalised patients report a wide effect range, from a decreased adjusted OR for mortality of 0.60 (95% CI 0.42 to 0.85) in the retrospective cohort of Albani et al 70 to a non-significantly increased adjusted OR of 1.30 (95% CI 0.65 to 2.64) in Kuderer et al 71 Even more heterogeneity is seen in studies that assess the addition of azithromycin to hydroxychloroquine, with a survival benefit (adjusted HR of 0.294; 95% CI 0.218 to 0.396) seen by Arshad et al, 72 opposed to a significantly increased 30-day mortality (adjusted OR 2.93; 95% CI 1.79 to 4.79) reported again by Kuderer et al 71 In an outpatient setting, Guérin et al 73 reported a significant reduction in the mean time to clinical recovery with azithromycin (12.9 days with azithromycin vs 25.8 days without; p<0.0001). A significant difference in hospitalisation risk was, however, not withheld by Szente et al 74 (adjusted OR for azithromycincontaining vs no-azithromycin-containing regimens 0.93; 95% CI 0.72 to 1.90).…”
Section: Covid-19mentioning
confidence: 99%
“…As noted above, several recent studies have attempted to explore the role of hydroxychloroquine earlier in the clinical course of COVID-19 [12][13][14][15][16]. However, given enrollment of generally younger patients with low baseline rates of hospitalization, these studies appear underpowered to demonstrate meaningful effects.…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian study of 636 symptomatic, but virology unconfirmed patients treated by telemedicine at home, also noted a reduction in hospitalization rate (5.4% vs 1.9%), with the greatest reductions occurring among the patients who started hydroxychloroquine therapy within the first 7 days of symptoms [14]. A small French report noted a reduction in symptoms with early therapy compared to observation [15]. Finally, a German report of 141 outpatients, when compared to cases in the community, noted a decrease in hospitalization rate (2.8% vs 15.4%) with a combination of hydroxychloroquine, azithromycin and zinc [16].…”
Section: Introductionmentioning
confidence: 99%